2004
DOI: 10.1161/01.cir.0000124226.88860.55
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Treatment Attenuates Neointimal Thickening With Enhanced Expression of Heat-Shock Protein 72 and Suppression of Oxidative Stress

Abstract: Background-The beneficial effects of thermal therapy have been reported in several cardiovascular diseases. However, it is unknown whether the thermal treatment has some beneficial roles against the development of atherosclerosis. Methods and Results-The inflammatory arterial lesion was introduced by placement of a polyethylene cuff on femoral arteries of male Sprague-Dawley rats for 4 weeks. Thermal-treated group underwent daily bathing in 41°C hot water for 15 minutes. Neointimal thickening along with immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 55 publications
3
37
0
Order By: Relevance
“…Some of these regulators can reduce atherosclerosis via preventing neo intimal hyperplasia. Relevant to the current study is the observation that heat treatment can inhibit neo-intima growth [31][32][33]. Interestingly, elevation in HSP72 (which has high homology with HSPA6) has been associated with the heat shock reduction in smooth muscle cell proliferation after trauma [31].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 71%
See 2 more Smart Citations
“…Some of these regulators can reduce atherosclerosis via preventing neo intimal hyperplasia. Relevant to the current study is the observation that heat treatment can inhibit neo-intima growth [31][32][33]. Interestingly, elevation in HSP72 (which has high homology with HSPA6) has been associated with the heat shock reduction in smooth muscle cell proliferation after trauma [31].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 71%
“…Interestingly, elevation in HSP72 (which has high homology with HSPA6) has been associated with the heat shock reduction in smooth muscle cell proliferation after trauma [31]. Two studies demonstrated that thermal treatment of arterial tissues in vitro and in vivo caused a reduction in media growth, leading to a prevention of arterial restenosis [33,34]. In one study hyperthermia at 43 o C was effective in suppressing rat vascular SMC proliferation in vitro by causing cell cycle arrest without causing cell death and not affecting endothelial cells which are normally damaged after angioplasty [34].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…1 However, recent findings suggest that the adventitia is an active layer that could play an important role in the physiological regulation of arterial smooth muscle tone, 2-5 modulating the response to stimuli such as noradrenalin and angiotensin II, and regulating nitric oxide release from the endothelium, thus counterbalancing the vasoconstrictor effects on smooth muscle cells. 6 An active role of the adventitia in determining arterial properties has been proposed in pathological states such as atherosclerosis 7 and systemic hypertension, 8 and in arterial wall remodeling. 2,9, 10 …”
mentioning
confidence: 99%
“…In this study, heat therapy on patients with type 2 DM through hot tub immersion six days a week for three consecutive weeks dropped their fasting plasma glucose and mean glycosylated hemoglobin levels (Hooper, 1999). Although the HSP levels were not measured in this trial, it documented an average rise of 0.8°C in body temperature, which is sufficient for HSP induction (Okada et al, 2004). Despite the lack of proper controls and its exploratory nature, the credibility of this early report has been substantiated by similar studies from animal models of DM.…”
Section: Hsp Inhibits Inflammation and Stress Kinasesmentioning
confidence: 84%